Assessing Genetic Diversity and Population Structure of Western Honey Bees in the Czech Republic Using 22 Microsatellite Loci - Aleš Knoll; Martin Šotek; Jan Prouza; Lucie Langová; Antonín Přidal; Tomáš Urban (Insects)
To date, no study has been conducted to investigate the diversity in honeybee populations of Apis mellifera in the Czech Republic. Between 2022 and 2023, worker bees were collected from colonies distributed throughout the Czech Republic in 77 districts, and their genetic differences were examined using 22 microsatellite loci. The samples were obtained from hives (n = 3647) and through the process of capture on flowers (n = 553). Genetic diversity parameters were assessed for both populations in all 77 districts. The findings demonstrated that honeybee populations exhibit moderate genetic diversity, as evidenced by the number of observed alleles, the Shannon index, and heterozygosity values. There was no discrepancy in diversity between hive and flower samples. Diversity characteristics were determined: mean observed heterozygosity 0.55 (hives) and 0.56 (flowers), and fixation index 0.58 for both populations. The average number of alleles per locus was 13.77 and 11.18 from hives and flowers, respectively. The low FST and FIS values (they measured the level of genetic differentiation between populations and the level of inbreeding, respectively) suggest the absence or minimal genetic diversity within and among studied populations. The genetic variation was calculated as 2% and 1% between populations, 8% and 6% between individuals within populations, and 91% and 93% between all individuals in samples from hives and flowers, respectively. Cluster and DAPC (discriminant analysis principal component) analysis classified the bee samples collected from across the country into three and five to six distinguishable groups, respectively. The honeybee population in the Czech Republic displays sufficient diversity and a partial structure. However, there appears to be no correlation between the genetic groups and the geographic regions to which they are assigned.